2022
DOI: 10.1111/pde.15020
|View full text |Cite
|
Sign up to set email alerts
|

The common triggers of urticaria in children admitted to the pediatric emergency room

Abstract: Background Urticaria frequently causes pediatric emergency department (PED) admissions. Children with urticaria may unnecessarily avoid suspected allergens. We aimed to investigate the possible and exact triggers of urticaria in children admitted to the PED. Methods Medical records of children admitted to the PED within a 1‐year period were evaluated for the International Classification of Diseases 10 (ICD‐10) L50 urticaria code, noting symptoms, and possible triggers of urticaria. We performed telephone inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
3
0
0
2
Order By: Relevance
“…Our study found that the majority of infants who present with urticaria of unknown etiology have AU and experience resolution even if the cause remains unidentified. Our results are consistent with prior studies in older children which showed that underlying etiology is unidentified in approximately half of pediatric AU and CU cases, even if further laboratory workup (e.g., complete blood count, IgE test, autologous serum skin test, and thyroid studies) is pursued 7,8 . In our cohort, food allergy and infection were two most common AU etiologies eventually identified, which is consistent with prior literature 2,8 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found that the majority of infants who present with urticaria of unknown etiology have AU and experience resolution even if the cause remains unidentified. Our results are consistent with prior studies in older children which showed that underlying etiology is unidentified in approximately half of pediatric AU and CU cases, even if further laboratory workup (e.g., complete blood count, IgE test, autologous serum skin test, and thyroid studies) is pursued 7,8 . In our cohort, food allergy and infection were two most common AU etiologies eventually identified, which is consistent with prior literature 2,8 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with prior studies in older children which showed that underlying etiology is unidentified in approximately half of pediatric AU and CU cases, even if further laboratory workup (e.g., complete blood count, IgE test, autologous serum skin test, and thyroid studies) is pursued. 7,8 In our cohort, food allergy and infection were two most common AU etiologies eventually identified, which is consistent with prior literature. 2,8 Our data support the latest clinical guidelines for adult and pediatric urticaria, which recommend allergy tests for AU only in the context of appropriate clinical history.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…3 Drugi vodeći uzročnik AU jesu IgEpo sredovane reakcije na nutritivne alergene (proteini kravljeg mlijeka, jaja, kikiriki, orašasti plodovi, riba), aditive u hrani (Na benzoati, salicilati, umjetne arome, boje), lijekove (betalaktamski i drugi antibiotici, anal getici, opioidi, kontrastna sredstva za snimanje). 3,4 AU je u većini slučajeva samoizlječiva bolest benignog tije ka. Kod dokazanog alergijskog uzročnika AU u terapi ju se uvode antihistaminici druge generacije, 5 no ako se dokaže bakterijska infekcija betahemolitičkim streptokokom grupe A ili Mycoplasmom pneumoniae, potrebno je provesti antimikrobno liječenje.…”
Section: Akutna Urtikarijaunclassified
“…2,3 Smatra se kako 1% djece godišnje razvije simptome urtikarije. 4 Diferen cijalno dijagnostički, urtikariju se mora razlikovati od drugih stanja poput anafilaksije, mastocitoze, autoin flamatornih sindroma, urtikarijalnog vaskulitisa, sin droma aktivacije makrofaga ili bradikininom posredo vanog angioedema, koja se također mogu prezentirati istom ili sličnom kliničkom slikom, no zbog jasno raz ličitoga patofiziološkog mehanizma nastanka ne ubra jaju se u podtipove urtikarija. 1,3 Prema vremenu na stanka urtikariju dijelimo na akutnu i kroničnu, a kro ničnu urtikariju dijelimo dalje u podtipove ovisno o uzročniku.…”
unclassified